Analisis determinan daya saing daerah Kabupaten/Kota di Provinsi Jambi - Nurjanah, Rahma; Anasthasia Silitonga, Ruth; Mustika, Candra (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to: 1) analyze the level of competitiveness of regencies/cities in Jambi Province. 2) analyze the influence of the Regional Expenditures, Revenue Sharing Funds, Remaining Budget Financing (SiLPA), Investments and Regional Original Income on the level of competitiveness of regencies/cities in Jambi Province. This study used secondary data in 2015-2019. The methods used are descriptive and quantitative methods using panel data analysis tools. This study found that: 1) during the 2015-2019 period the level of competitiveness of the regencies/cities in Jambi Province occupies Tanjung Jabung Barat Regency as an area that has a superior and strong level of regional competitiveness because the index value of the regional competitiveness level of Tanjung Jabung Barat Regency greater than one. 2) the variable Regional Expenditures, Revenue Sharing Funds and Excess Budget Financing partially and simultaneously have a significant positive effect on the level of competitiveness of regencies/cities in Jambi Province. While the variable Investment and Original Regional Revenues partially have a no significant effect on the level of competitiveness of regencies/cities in Jambi Province.